Chromosome Painting Provides Insights Into the Genome Structure and Evolution of Sugarcane - Meng, Zhuang; Wang, Qinnan; Khurshid, Haris; Raza, Ghulam; Han, Jinlei; Wang, Baohua; Wang, Kai (Frontiers in Plant Science, 2021)
The genus Saccharum is composed of species with high polyploidy and highly varied chromosome numbers, laying a challenge for uncovering its genomic structure and evolution. We developed a chromosome 2 painting (CP2) probe by designing oligonucleotides covering chromosome 2 of Saccharum spontaneum (2n = 8x = 64). Fluorescence in situ hybridization (FISH) using this CP2 probe revealed six types of ploidies from twenty S. spontaneum clones, including 6x, 8x, 10x, 11x, 12x, and 13x clones. The finding of S. spontaneum clones with uneven of ploid suggested that certain S. spontaneum clones come from hybridization. It renews our knowledge that S. spontaneum is derived from autopolyploidization. Combined with a S. spontaneum-specific probe, chromosome 2-derived chromosome or fragments from either S. spontaneum or Saccharum officinarum can be identified in sugarcane modern cultivars. We revealed unexpected high level of interspecific recombination from introgressive S. spontaneum chromosomes (>50.0%) in cultivars ROC22 and ZZ1, indicating frequent chromosome exchange in cultivars. Intriguingly, we observed interspecific recombination recurring among either homoeologous or non-homoeologous chromosomes in sugarcane cultivars. These results demonstrated that chromosome painting FISH is a powerful tool in the genome dissection of sugarcane and provide new insights into the genome structure and evolution of the complex genus Saccharum.